2022
DOI: 10.1021/acssuschemeng.2c06144
|View full text |Cite
|
Sign up to set email alerts
|

Providing Natural Organic Pigments with Excellent Tanning Capabilities: A Novel “One-Pot” Tanning–Dyeing Integration Strategy for Sustainable Leather Manufacturing

Abstract: Engineering high-performance chrome-free colored leather is currently a tough challenge in the leather industry. Herein, we report on a novel tanning−dyeing integration strategy based on converting natural cochineal carmine (Car) into an effective tanning agent (DCar) without losing its dyeing capabilities via periodate oxidation. Initially, DCar was used as a tanning−dyeing agent, leading to tanned-dyed leather with well-dispersed and fixed collagen fibers (CFs) and a shrinkage temperature (T s ) of ca. 70 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…54 Moreover, the signal intensity attributed to carboxyl groups (1743 cm −1 ) in L1 was greater than that in PS and R1, suggesting that LP could interact well with carboxyl groups on collagen. 47 XPS was employed to further investigate the changes that occurred in collagen during tanning (Figure 9c New peaks in R2 and L2 spectra (530.09 and 530.56 eV, respectively) were attributed to the coordination of Al 3+ /Zr 4+ with oxygen on collagen, indicating that Al 3+ /Zr 4+ tanning agents formed strong interactions with carboxyl groups on collagen. 55,56 As for N 1s, deconvolution peaks were observed at 399.03 and 399.60 eV.…”
Section: Structure Analysis Of Rl and Lps [Eoa]mentioning
confidence: 99%
“…54 Moreover, the signal intensity attributed to carboxyl groups (1743 cm −1 ) in L1 was greater than that in PS and R1, suggesting that LP could interact well with carboxyl groups on collagen. 47 XPS was employed to further investigate the changes that occurred in collagen during tanning (Figure 9c New peaks in R2 and L2 spectra (530.09 and 530.56 eV, respectively) were attributed to the coordination of Al 3+ /Zr 4+ with oxygen on collagen, indicating that Al 3+ /Zr 4+ tanning agents formed strong interactions with carboxyl groups on collagen. 55,56 As for N 1s, deconvolution peaks were observed at 399.03 and 399.60 eV.…”
Section: Structure Analysis Of Rl and Lps [Eoa]mentioning
confidence: 99%
“…Ding et al reported the synthesis of a cochineal carmine dialdehyde by periodate oxidation, which was used as a tanning agent as well as a dye. 182 Gao et al produced Al-oligosaccharide by microwave-assisted AlCl 3 /H 2 O 2 oxidation, which produced aldehyde and carboxyl groups in the oligosaccharide. 183 Similarly, Wang et al reported the tanning of leather with triglycidyl isocyanurate-modifiedstarch.…”
Section: Sustainable and Eco-friendly Chromefree Tanning Processesmentioning
confidence: 99%
“…E-mail: liuxinhua@sust.edu.cn water treatment, achieving energy savings and emission reduction. 15,17,18 For product scale application, brightness and washing resistance performance of the color of the leather surface are critical indicators to evaluate the quality of finished leather, which directly affects the application range and service life of leather products. 19,20 At the moment, anionic dyes are commonly used in leather dyeing and can penetrate and distribute evenly in traditional chrome-tanned leather.…”
Section: Introductionmentioning
confidence: 99%
“…14–16 According to this viewpoint, if chemical additives for retanning/fatliquoring/dyeing functions can be produced without affecting the quality of finished leather, different wet finishing processes can be completed within one process, effectively reducing energy consumption and wastewater treatment, achieving energy savings and emission reduction. 15,17,18…”
Section: Introductionmentioning
confidence: 99%